2011
DOI: 10.1111/j.1439-0485.2011.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and depth distribution of microepiphytes on Posidonia oceanica (L.) Delile leaves in a meadow off Tunisia

Abstract: A survey on the epiphytic microorganisms growing on Posidonia oceanica leaves was conducted along a depth transect along the coast of Eastern Tunisia (Mahdia). Samples were collected by SCUBA diving at depths of 3, 5, 10 and 12 m in July 2008 and January 2009. A total of 58 microepiphyte taxa were identified. Multivariate analyses revealed temporal and spatial variation of the abundance of epiphytic microalgae. Water motion, light availability, temperature and motility of species seem to be responsible of temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 65 publications
(152 reference statements)
5
47
0
Order By: Relevance
“…Some types of vegetation, such as Posidonia oceanica, were present throughout the year; others such as Padina pavonica, Cystoseira mediterranea and Halophila stipulacea, appeared for a few months. P. oceanica, a perennial species, showed a rather good vitality in the study area, as was confirmed by several previous studies (Mabrouk et al 2009(Mabrouk et al , 2011.…”
Section: Data Sampling and Processingsupporting
confidence: 74%
See 1 more Smart Citation
“…Some types of vegetation, such as Posidonia oceanica, were present throughout the year; others such as Padina pavonica, Cystoseira mediterranea and Halophila stipulacea, appeared for a few months. P. oceanica, a perennial species, showed a rather good vitality in the study area, as was confirmed by several previous studies (Mabrouk et al 2009(Mabrouk et al , 2011.…”
Section: Data Sampling and Processingsupporting
confidence: 74%
“…This species has been reported as a widespread dinoflagellate in many coastal waters and estuaries around the world, generally in summer and autumn (Levasseur et al 2003), in the Fleet lagoon in the UK (Foden et al 2005), in Greek coastal waters (Aligizaki et al 2009), along the coast and inside the harbours of the Abruzzo region in the Adriatic Sea (Ingarao et al 2009), and on the northern coasts of Tunisia (Aissaoui et al 2014). In the study area, it reached about 25000 cells g -1 FW on Posidonia leaves, which is higher than the 70 cells g -1 FW found in the same area by Mabrouk et al (2011). However, these concentrations were lower than those reported for Cymodocea nodosa in Greece, where the abundance reached 133000 cells g -1 FW (Aligizaki et al 2009).…”
Section: Discussionmentioning
confidence: 43%
“…The shacking procedure was repeated several times to ensure that most of the attached organisms were separated. This method was used by previous researchers to remove microepiphytic species (Mabrouk et al, 2011). Thereafter, the samples were passed through 100 µm mesh sieves to remove host algae and large particles and were completed to 50 ml to obtain a concentrate of microalgae, which were finally preserved with 4% neutralized formalin.…”
Section: Separation Of Epiphytic Microalgaementioning
confidence: 99%
“…Three sampling stations 2 km distant from each other were chosen in August 2009 when the P. oceanica microepiphytic community reached its maximum abundances and diversity (Aligizaki and Nikolaidis 2006, Turki 2005, Mabrouk et al 2011.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Seagrass epiphytes are known to be even more sensitive to environmental changes than the plant hosts (Nesti et al 2009). Epiphytic microalgae composition, in particular, is influenced by abiotic factors such as temperature (Aligizaki and Nikolaidis 2006;Turki 2005), light, salinity, and nutrient availability (Armitage et al 2006) and biotic factors such as grazing (Mazzella and Russo 1989), shoot length, density and morphology of the host plant (Sirota and Hovel 2006, Chung and Lee 2008, Mabrouk et al 2011. Nutrient over-enrichment caused by anthropogenic activities has been associated with the shift of the structure of microepiphytic assemblages (Armitage et al 2006) and the decline of seagrass (Green and Short 2003, Orth et al 2006, Ben Brahim et al 2010.…”
Section: Introductionmentioning
confidence: 99%